The Impact of Dietary Components on Lactation: A Critical Review - Rachana Jagadeesh; Rohit Kumar; Neelesh Kumar Maurya (International Journal of Nutritions, 2024)
Infant growth and well-being depend on an adequate and species-specific amount of nutrients, antibodies, and immunological components, which are provided by human breastfeeding, the cornerstone of newborn sustenance and development However, some moms struggle with producing inadequate milk, which can put the health advantages of nursing for both mother and child in jeopardy and cause stress, anxiety, and perhaps early weaning. This review discusses the fascinating idea that food changes might be a healthy, natural way to promote breastfeeding. Researcher will carefully review the available scientific data about the potential effects of several dietary groups—such as grains, legumes, fruits and vegetables, herbs, spices, and vegetables—on human milk production. The evidence supporting the use of certain dietary components as "galactagogues" in some traditional practices to enhance milk production differs. The present article will study the processes by which these foods may affect breastfeeding, taking into account the limitations of previous studies and the need for additional study. In addition, the aim of this study is to elucidate the processes underlying the putative galactogenic properties of various dietary components. While folklore and history suggest that certain foods can promote breastfeeding, thorough scientific research is needed to determine their true effectiveness and safety. The aim of this review is to critically examine the current literature, identify research gaps and provide evidence-based insights into food choices to improve nursing practice. Ultimately, understanding how breastfeeding interacts with maternal nutrition can help moms overcome barriers to breastfeeding and promote their own and their infants’ health and well-being.
Keywords: Boost Lactation; Dietary Components; Herbs; Milk Production; Pulses And Cereals; Vegetables